Physics projects for young scientists - Goodwin, Peter, 1951- (New York : F. Watts, 1991)
Gives instructions for and explains the principles behind a variety of simple physics experiments.
Includes bibliographical references and index.
School Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Junior High School.
7-10.
Young Adult
Keywords: Physics -- Experiments -- Juvenile literature; Physics -- Experiments -- Methodology -- Juvenile literature; Experiments; Physics -- Experiments; Physics -- Experiments; Science -- Experiments